The crusade for forgotten souls : reforming Minnesota's mental institutions, 1946-1954 - Foote, Susan Bartlett (University of Minnesota Press, 2018)
"The Crusade for Forgotten Souls recounts Minnesota's reform movement that broke the stigma surrounding mental illness, publicized the painful truth about the state's asylums, and resulted in the first legislative steps toward a modern mental health system. Susan Bartlett Foote tells the story of the early advocates for compassionate care of the mentally ill who made the crusade a success"--Provided by publisher.